A fragility approach to sustainability – researching effects of education. Issue 7 (4th November 2019) - Platje, Joost (Johannes); Will, Markus; Van Dam, Ynte K.
Abstract : Purpose: Management education trainers are increasingly called upon to train students to devise interventions for sustainable development in business settings. Due to the dominant reductionist paradigm, these interventions may lead to unwanted side effects. Teaching students about unacknowledged feedback loops in complex systems should prevent them from choosing "the most obvious" intervention without considering unwanted side effects.The current study aims to report the effects of teaching a systems perspective, applied to transport systems, on students' opinions and expressed paradigms. The following questions are addressed: Do students adhere to the techno-centric paradigm, believing technology, innovation and growth can solve all types of threats for sustainable development, while neglecting low probability, high impact events? Are paradigms held by students coherent? Can teaching lead to a change in opinions and paradigms held by students? Design/methodology/approach: Measures for several systems concepts (i.e. functional stupidity, paradigms and fragility) are taken across a wide sample of university students. Posttests of some key items are taken for a subsample that followed a sustainability and systems perspective in a course on transport economics. Findings: A large share of students think that technology can solve different types of problems in sustainable development (a kind of weak sustainability), but their paradigms tend to be a mix of conflicting opinions. Though student opinions on topics that were explicitly treated in the course have changed, neither a wider paradigm shift nor significantly more coherent paradigms can be confirmed. Originality/value: The results show that even though students can be taught about the unwanted side effects and limitations on specific techno-fix interventions, this does not automatically translate into a critical mind-set toward techno-fixing in general.